(untitled)
The migration of plaice (Pleuronectes platessa ) in relation to the environment Behavioral adjustment of fishes to release into a new habitat The feeding behavior and ecology of marine fish larvae Chemical senses, chemical signals, and feeding behavior in fishes.
Keywords: Cá; Hành vi,Behavior; Fishes,Fishery management